2012
DOI: 10.1590/s0104-66322012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, spectroscopical and thermal characterization of biodiesel obtained by enzymatic route as a tool to select the most efficient immobilized lipase

Abstract: -Two microbial lipases from Burkholderia cepacia and Pseudomonas fluorescens were evaluated as catalysts for the enzymatic transesterification of beef tallow with ethanol and the most efficient lipase source was selected by taking into account the properties of the product to be used as fuel. Both lipases were immobilized on an epoxy silica-polyvinyl alcohol composite by covalent immobilization and used to perform the reactions under the following operational conditions: beef tallow-to-ethanol molar ratio of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…The calibration curves were generated with standard ethyl esters using hexanol as the internal standard. The reaction yield was calculated by taking into account the mass of ester content obtained by GC analysis and the total theoretical ester mass based on the initial amount of both oil and ethanol (Urioste et al, 2008;Silva et al, 2012).…”
Section: Monitoring Ethyl Ester Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration curves were generated with standard ethyl esters using hexanol as the internal standard. The reaction yield was calculated by taking into account the mass of ester content obtained by GC analysis and the total theoretical ester mass based on the initial amount of both oil and ethanol (Urioste et al, 2008;Silva et al, 2012).…”
Section: Monitoring Ethyl Ester Formationmentioning
confidence: 99%
“…The temperature was maintained at 20 °C during the assays. Biodiesel samples of 2.0 mL were used, and the measurements replicated three times (Silva et al, 2012).…”
Section: Viscosity and Density Determinations Of Purified Fatty Acid mentioning
confidence: 99%
“…Covalent attachment of nucleophilic groups of lipases (N-terminal and hydroxyl groups) on highly activated supports (e.g., epoxy or aldehyde groups on the support surface introduced after the activation step) may promote the stabilization of their three-dimensional structures, thus reducing possible conformational changes induced by any distorting agents such as solvents and temperature [18, 2124]. Previous studies carried out in our lab have reported the preparation of robust biocatalysts prepared by covalent attachment of several lipases on activated hybrid support SiO 2 -PVA for further application in biotransformation reactions [21, 22, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…The most suitable conditions were FAD to methanol molar ratio of 1:6 and a reaction temperature of 300 °C during 30 min, in which 95% of FAMEs was produced. Compared to the conventional acid-catalyzed esterification of FAD using a similar molar ratio, they found that only a 75% yield was obtained in 5 h. Silva et al (2012) obtained biodiesel from beef tallow with ethanol, reaching reaction times between 24-48 hours at 45 °C. The authors used an enzymatic route with two different lipases.…”
Section: Heterogeneous and Enzymatic Catalystsmentioning
confidence: 99%